Who Cares? Supplier Reactions to Buyer Claims after Psychological Contract Over‐Fulfillments. Issue 4 (8th November 2019) - Esslinger, Jens; Eckerd, Stephanie; Kaufmann, Lutz; Carter, Craig
Abstract : Buyer–supplier engagement leads to numerous opportunities for unexpected positive benefits to occur. How these events come about and are managed (i.e., what entities are responsible for the outcomes and how the benefits are shared) remains an under‐investigated phenomenon in the supply chain literature. This research uses attribution theory and a systems thinking perspective to investigate a supplier's experience of psychological contract over‐fulfillment followed by a buyer claim. We hypothesize that a supplier's reaction to a buyer's claim depends on whether the type of claim (economic versus social) fits with the locus of causality the over‐fulfillment is attributed to: (1) the buying organization ( buyer‐only attributions ), (2) the buyer and the supplier jointly ( dyad attributions ), or (3) a third party in the buyer's innovation network ( buyer‐network attributions ). Results from a multi‐stage scenario‐based experiment suggest that following the supplier's experience of psychological contract over‐fulfillment, the supplier's trust toward the buyer is highest for dyad attributions, while the supplier's appreciation for the buyer's network is highest with dyad and buyer‐network attributions. Once the buyer claims value, however, the influence of attributions diminishes. While social reward claims had almost no impact on relational outcomes, economic reward claims significantly harm the supplier's perceptions of the buyer. Regardless of the type of claim, the locus of causality was largely irrelevant for the supplier's reaction to the buyer's reward claim. Our study contributes to the supply chain psychological contract literature by investigating positive over‐fulfillments of the psychological contract, as opposed to previous literature that has focused on negative breaches. We also extend attribution theory by introducing a novel supply chain‐specific attribution for the locus of causality, and we establish boundary conditions of attribution theory in the face of supply chain‐typical claiming mechanisms. For managers, locus of causality for a positive event seems to be irrelevant once claiming sets in.